2020
DOI: 10.4314/ajesms.v16i1.1
|View full text |Cite
|
Sign up to set email alerts
|

GeoGebra integration and effectiveness in the teaching and learning of mathematics in secondary schools: A review of literature

Abstract: This article explores studies that investigated GeoGebra integration and its effectiveness in teaching and learning mathematics. The study examines existing studies on how and why GeoGebra enhanced students’ performance; understanding, analytical thinking, generalization, abstract thinking, representation, and logical thinking. By a deep exploration of the main construct of the study, we collected and analyzed 20 studies whose results reported that GeoGebra added values when applied in teaching and learning in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 8 publications
1
5
0
5
Order By: Relevance
“…However, this improvement may depend on the teaching method. This finding is in agreement with Arbain and Shukor (2015), Mathevula and Uwizeyimana (2014), Niyukuri et al (2020), Ocal (2017) and Uwurukundo et al (2020), whose studies found that ICT, in general, could improve the way students perform in geometry, and that GeoGebra software is effective in improving students' achievement and attitudes towards geometry. In this study, the ICT factor had improved attitude scores in the experimental group, because the teachers of this group used GeoGebra in lessons, while the traditional class did not use this ICT-based software and showed no improvement in attitude.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…However, this improvement may depend on the teaching method. This finding is in agreement with Arbain and Shukor (2015), Mathevula and Uwizeyimana (2014), Niyukuri et al (2020), Ocal (2017) and Uwurukundo et al (2020), whose studies found that ICT, in general, could improve the way students perform in geometry, and that GeoGebra software is effective in improving students' achievement and attitudes towards geometry. In this study, the ICT factor had improved attitude scores in the experimental group, because the teachers of this group used GeoGebra in lessons, while the traditional class did not use this ICT-based software and showed no improvement in attitude.…”
Section: Discussionsupporting
confidence: 89%
“…The REB (2016) recommends that ICT tools are integrated into the learning of mathematics in secondary schools, due to the importance of mathematics for several technology and science domains. In a review of literature, Uwurukundo et al (2020) explain that mathematics domains include geometry, algebra, calculus, and trigonometry, and argue that students can explore the software and acquire mathematics knowledge more independently than students who are subjected to traditional learning methods. The expectation is that exposing students to new technology for teaching and learning of mathematics improves their competencies and achievement, both in the classroom and in their daily lives (Mathevula & Uwizeyimana, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Classrooms are booming, buzzy and exciting, fascinating places, anchored in bigger systems of schools and traditions (e.g., Brown, 1992), and changing their teacher and procedural-oriented methods is a difficult and complex process with variable results. According to Uwurukundo et al (2020), while GeoGebra programs are typically beneficial, their effectiveness is contingent on how they are integrated into the teaching and learning process. In general, as digital programs strive to scale larger, their effect sizes appear to shrink (Drijvers, 2019).…”
Section: Introductionmentioning
confidence: 99%